Analysis and evaluation of law number 12 of 2012 concerning higher education based on sports needs for students - Sandey Tantra Paramitha; Muhamad Fahmi Hasan; Leni Anggraeni; Marisa Noviyanti Fajrah Ilsya; Muhamad Gilang Ramadhan; Apriya Maharani Rustandi; Hikmat Kodrat (Jurnal Civics: Media Kajian Kewarganegaraan, 2021)
The sense of responsibility to educate students as "whole people" which lies on the shoulders of all higher education managers, sports programs will continue to have strategic programs in the higher education system in Indonesia. Therefore, researchers conducted a normative and juridical literature review to examine sports in higher education. The results of this review indicate that Article 35 (3) of the Higher Education Curriculum Law No. 12 of 2012 concerning sports higher education is needed to be used as a compulsory subject in higher education. Overall, this review provides an appropriate reference point for further research by identifying the need for research in the aspect of sports needs, especially making sports a compulsory subject in college as a form of realizing a whole human being. However, there are weaknesses and inequalities in several aspects. This research is a novelty in the study of sports policy analysis in Indonesia.